TINGKAT KEPUASAN KONSUMEN TERHADAP PELAYANAN DI RESTORAN KINAMANG MANADO - Jhudhita Dace Rumondor; Celsius Talumingan; Rine Kaunang (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
The objective of this research is to know the level of customer satisfaction with service at Kinamang Restaurant. This research was conducted in March to June 2019. The research used primary data obtained directly from the object of research, namely data obtained from consumers of Kinamang Manado Restaurant through direct interviews with 30 respondents using a questionnaire prepared as well as secondary data. obtained through books, journals, and literature-literature relating to this research. Methods data collection is done by using a survey, measured by a Likert scale. The research result showed that the level of consumer satisfaction with the service at Restoran Kinamang from the service variable was 79.53%, generally classified as neutral. In particular, the level of consumer satisfaction with the service at Restoran Kinamang for the satisfied category was at 85.66% responsiveness and 84.66 empathies and 80% confidence, for the neutral category which was real evidence of 78%, and service reliability 68%.Â Keyword:Â  Satisfaction, Consumer, Kinamang Restaurant, Likert Scale